Digital transformation of professions in physical education and sport sector - Ermakov, A.V.; Skarzhynska, E.N.; Novoselov, M.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to reveal the trends of transformation of tracks of the professional physical education and sports specialist training system in the context of the ongoing economic digitalization process and data-driven management approach of the physical education and sports experts. Methods and structure of the study. We made a content analysis of 135,000 documents (including study reports and corporate sports management vacancies in Europe, North and South America) to rank requirements to the competences and job responsibilities in special digital services of the modern physical education and sport sector service personnel. Results and conclusion. On the whole, the global physical education and sport sectors show a special demand for personnel having digital competences and, therefore, we recommend the national physical education and sport sector decision-makers to give a special priority to the following education disciplines: “SMM in sports", "Customer Relationship Management incorporate sports", "Digital Marketing in Sports", "Artificial Intelligence in physical education and sports", "Digital technologies in sports"; ; plus the following special modules: "Data analysis in sports", "Artificial Intelligence and machine learning in sports", "Digital project management in sports", "Big Data with artificial Intelligence technologies", etc.